Systematic Literature Review: A Study of Academic Burnout among Undergraduate Students in Universities - Atika Rahmania El Barusi; Farida Kurniawati (Sultan Publisher, 2024)
Research on burnout has flourished within the educational environment or academic settings, with academic burnout gaining significant attention in recent decades. This systematic review aims to synthesize evidence from previous studies regarding the depiction and influencing factors of burnout among undergraduate students. The search strategy adhered to the PRISMA guidelines and was based on the following keywords: